2008
DOI: 10.1097/qai.0b013e318186eaa4
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Chemokine Receptor Polymorphisms With HIV-1 Mother-to-Child Transmission in Sub-Saharan Africa: Possible Modulation of Genetic Effects by Antiretrovirals

Abstract: Background-HIV-1 mother-to-child transmission (MTCT) remains an important route of infection in sub-Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
5
22
0
Order By: Relevance
“…CX3CR1 745G>A variation alone may not have a significant role in HIV transmission. These observations are supported by a study involving three sub-Saharan countries, South Africa, Uganda and Malawi, which also failed to observe any association between CX3CR1 745G>A variation and HIV infection in children born to antiretroviral therapynaïve mothers [28]. The findings of the above study [28] may have been distorted by the heterogeneous samples drawn from the three different countries involved.…”
Section: Chemokine Receptor Polymorphism and Their Association With Hsupporting
confidence: 55%
See 1 more Smart Citation
“…CX3CR1 745G>A variation alone may not have a significant role in HIV transmission. These observations are supported by a study involving three sub-Saharan countries, South Africa, Uganda and Malawi, which also failed to observe any association between CX3CR1 745G>A variation and HIV infection in children born to antiretroviral therapynaïve mothers [28]. The findings of the above study [28] may have been distorted by the heterogeneous samples drawn from the three different countries involved.…”
Section: Chemokine Receptor Polymorphism and Their Association With Hsupporting
confidence: 55%
“…These observations are supported by a study involving three sub-Saharan countries, South Africa, Uganda and Malawi, which also failed to observe any association between CX3CR1 745G>A variation and HIV infection in children born to antiretroviral therapynaïve mothers [28]. The findings of the above study [28] may have been distorted by the heterogeneous samples drawn from the three different countries involved. In a separate study, this research group demonstrated differences in distribution of genetic variants among African populations; pooling samples from different countries in genetic association studies, therefore, may introduce bias [29].…”
Section: Chemokine Receptor Polymorphism and Their Association With Hsupporting
confidence: 55%
“…Genomic DNA extracted from dried blood spots using QIAamp DNA Mini Kit (Qiagen, Valencia, CA) was genotyped for CCR5-wt/Δ32, CCR5 -59029-G/A, CCR2-180 -G/A, SDF-1 -G/A, IL4-589-C/T, MCP-1-2518-A/G, MBL 2, APOE 2060-T/C and 2198-C/T (distinguishing ε2, ε3 and ε4 alleles), CCL3L2 copy number variants (CNVs), and CX 3 CR1 -745-G/A, -849-C/T polymorphisms using real-time PCR (LightCycler, Roche) as described previously [13, 20, 21]. These genetic variants were selected because each has previously been found to be associated with HIV-related disease progression and/or neurocognitive impairment.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, variations in the use of antiretrovirals may also alter the effect of host genetics on HIV-1 transmission, as observed in a recent study of an HIV-1 mother-to-child transmission population administered preventive antiretrovirals. 30 These results further suggest that demographic or behavioral variations might play a role in the observed differences in HIV acquisition vulnerability, although no demographic or behavioral variations related to the CD4 C868T SNP have been found to date. 31 In summary, this study demonstrates a null association between the CD4 C868T genetic polymorphism and an individual's susceptibility to HIV-1 acquisition in a Chinese population.…”
Section: Discussionmentioning
confidence: 77%